2015
DOI: 10.1177/0300985815610388
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Expression Profiles in Canine Cutaneous and Subcutaneous Mast Cell Tumors

Abstract: The receptor tyrosine kinase (RTK) KIT is a major focus of current research into canine mast cell tumors (MCTs). Little is known about the role of other RTKs, such as vascular endothelial growth factor receptors (VEGFRs) and platelet-derived growth factor receptors (PDGFRs). These RTKs are dysregulated in many human and animal cancers and are key regulators of tumor angiogenesis. The aims of this study were to assess the expression and activation (phosphorylation) status of KIT, VEGFR2, and PDGFR (α and β) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…A two-tiered (Kiupel and others 2011) and a three-tiered grading system (Patnaik and others 1984) are both currently used. Numerous histopathological proliferation indices and markers have also been utilised in attempt to better determine the biological behaviour of a MCT: argyrophilic nucleolar-organising regions (Bostock and others 1989, Scase and others 2006, Webster and others 2007, 2008), B-cell lymphoma 2 (BCL-2) gene and protein expression (Vascellari and others 2013), Ki-67 (Abadie and others 1999, Scase and others 2006, Ozaki and others 2007, Webster and others 2007, 2008, Maglennon and others 2008), KIT staining pattern, presence of mutations in KIT or alterations in other receptor tyrosine kinases (Zemke and others 2002, Kiupel and others 2004, Webster and others 2007, 2008, Thompson and others 2015), minichromosome maintenance protein 7 (Berlato and others 2012), mitotic index (Bostock and others 1989, Sakai and others 2002, Elston and others 2007, Romansik and others 2007, Vascellari and others 2013, Van Lelyveld and others 2015), tumour suppressor in lung cancer 1 (Taylor and others 2010) and combinations of multiple markers or indices (Simoes and others 1994, Séguin and others 2006). …”
mentioning
confidence: 99%
“…A two-tiered (Kiupel and others 2011) and a three-tiered grading system (Patnaik and others 1984) are both currently used. Numerous histopathological proliferation indices and markers have also been utilised in attempt to better determine the biological behaviour of a MCT: argyrophilic nucleolar-organising regions (Bostock and others 1989, Scase and others 2006, Webster and others 2007, 2008), B-cell lymphoma 2 (BCL-2) gene and protein expression (Vascellari and others 2013), Ki-67 (Abadie and others 1999, Scase and others 2006, Ozaki and others 2007, Webster and others 2007, 2008, Maglennon and others 2008), KIT staining pattern, presence of mutations in KIT or alterations in other receptor tyrosine kinases (Zemke and others 2002, Kiupel and others 2004, Webster and others 2007, 2008, Thompson and others 2015), minichromosome maintenance protein 7 (Berlato and others 2012), mitotic index (Bostock and others 1989, Sakai and others 2002, Elston and others 2007, Romansik and others 2007, Vascellari and others 2013, Van Lelyveld and others 2015), tumour suppressor in lung cancer 1 (Taylor and others 2010) and combinations of multiple markers or indices (Simoes and others 1994, Séguin and others 2006). …”
mentioning
confidence: 99%
“…VEGFR2 and pVEGFR2 antibodies identified a major band at approximately 250 kDa, and minor bands of slightly lower molecular weight, as has been reported for human and canine neoplastic cells (Adham & Coomber ; Thompson et al . ). The c‐CBL blots showed a single specific band of approximately 100 kDa (Feshchenko et al .…”
Section: Resultsmentioning
confidence: 97%
“…Our results are also in line with a recent study that reported VEGFR2 expression (detected via western blot) in neoplastic cells isolated from some canine cutaneous and subcutaneous MCT (Thompson et al . ). These findings may help explain the success of KIT directed TKIs in tumours that lack mutated KIT (London et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations